Battery
Patent Information
- Application Number
- JP2023143131
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-04
- Publication Date
- 2025-03-14
AI Technical Summary
【0013】 本開示における電池は、軽量化を図りつつ、良好なクーロン効率を得ることができるという効果を奏する。
Smart Images

Figure 2025035833000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to batteries. [Background technology]
[0002] A battery usually has an electrolyte layer between a positive electrode active material layer and a negative electrode active material layer. In the field of batteries, a battery that utilizes a deposition-dissolution reaction of metallic lithium as a negative electrode reaction is known. For example, Patent Document 1 discloses that in a lithium solid state secondary battery that includes a negative electrode current collector, a solid electrolyte layer, a positive electrode active material layer, and a positive electrode current collector in this order, Cu, which is a metal that does not alloy with Li, is used as the material of the negative electrode current collector. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2016-035867 A Summary of the Invention [Problem to be solved by the invention]
[0004] In batteries that use the deposition and dissolution reaction of metallic lithium as the anode reaction, usually, no anode active material layer (layer containing anode active material particles) is provided during battery production, and the anode active material layer (Li-containing layer) is formed by initial charging, which has the advantages of making it easy to simplify the manufacturing process and to improve the energy density per volume. On the other hand, from the viewpoint of improving the energy density per weight, the use of a resin anode current collector (resin current collector) as the anode current collector has been considered.
[0005] Resin current collectors are lighter than metal current collectors, which allows for a reduction in the weight of the battery. However, resin current collectors have lower electronic conductivity than metal current collectors, which raises concerns that the use of resin current collectors may result in a decrease in Coulomb efficiency.
[0006] The present disclosure has been made in consideration of the above-mentioned circumstances, and has as its main object to provide a battery that is lightweight and can achieve good coulombic efficiency. [Means for solving the problem]
[0007] [1] A battery that utilizes a deposition and dissolution reaction of metallic lithium as a negative electrode reaction, a positive electrode having a positive electrode current collector and a positive electrode active material layer, a negative electrode having at least a negative electrode current collector, and an electrolyte layer disposed between the positive electrode and the negative electrode; the negative electrode current collector is a resin current collector, The battery, wherein the negative electrode has a first metal layer containing at least one of Mg and Ag between the negative electrode current collector and the electrolyte layer.
[0008] [2] The battery according to [1], wherein the negative electrode has a second metal layer containing at least one of Ni and Cu between the negative electrode current collector and the first metal layer.
[0009] [3] The battery according to [1] or [2], wherein the negative electrode current collector and the first metal layer constitute a coated current collector.
[0010] [4] The battery according to any one of [1] to [3], wherein the first metal layer contains Li.
[0011] [5] The battery according to any one of [1] to [3], wherein the first metal layer does not contain Li.
[0012] [6] The battery according to any one of [1] to [5], wherein the electrolyte layer is a solid electrolyte layer containing a solid electrolyte. Effect of the Invention
[0013] The battery according to the present disclosure has an effect of being lightweight and having good coulombic efficiency. [Brief description of the drawings]
[0014] [Figure 1] FIG. 1 is a schematic cross-sectional view illustrating a battery according to the present disclosure. [Diagram 2] FIG. 1 is a schematic cross-sectional view illustrating a battery according to the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The battery according to the present disclosure will be described in detail below with reference to the drawings. Each of the drawings shown below is a schematic illustration, and the size and shape of each part are appropriately exaggerated for ease of understanding.
[0016] 1 and 2 are schematic cross-sectional views illustrating a battery in the present disclosure. More specifically, FIG. 1 illustrates a battery before the first charge, and FIG. 2 illustrates a battery after the first charge. As shown in FIG. 1 and FIG. 2, the battery 10 has a positive electrode CA having a positive electrode current collector 1 and a positive electrode active material layer 2, a negative electrode AN having at least a negative electrode current collector 3, and an electrolyte layer EL disposed between the negative electrode AN and the positive electrode CA. The negative electrode current collector 3 is a resin current collector. Here, as shown in FIG. 1, in the battery 10, the negative electrode AN has a first metal layer 4A containing at least one of Mg and Ag between the negative electrode current collector 3 and the electrolyte layer EL. The negative electrode AN has a second metal layer 4B containing at least one of Ni and Cu between the negative electrode current collector 3 and the first metal layer 4A. Also, as shown in FIG. 1, in the battery 10 before the first charge, the first metal layer 4A usually does not contain Li. On the other hand, as shown in FIG. 2, in battery 10 after the initial charge, first metal layer 4A usually contains Li.
[0017] According to the present disclosure, the negative electrode has a resin current collector and a first metal layer containing a predetermined metal, and thus the battery can be made lightweight and have good coulombic efficiency. As shown in the above-mentioned Patent Document 1, it is known to use a metal current collector such as Cu as the negative electrode current collector. The metal current collector has a high density, so that the energy density per weight is small. In contrast, in the present disclosure, a resin current collector is used as the negative electrode current collector. The resin current collector is lighter than the metal current collector, so that the energy density per weight can be improved.
[0018] Here, as shown in the comparative example described later, when a resin collector is used, there is a concern that the Coulombic efficiency will be lower than when a metal collector is used. This is presumed to be because the resin collector has lower electronic conductivity than the metal collector. In contrast, the negative electrode in the present disclosure has a first metal layer containing at least one of Mg and Ag between the resin collector and the electrolyte layer. Typically, the resin collector is coated with the first metal layer to form a coated collector. By providing the first metal layer, good electronic conductivity can be obtained. Furthermore, Mg and Ag contained in the first metal layer can be alloyed with Li, respectively, and do not have a solid solubility limit. Therefore, Li ions can be stored well during charging. Therefore, it is presumed that good Coulombic efficiency can be obtained even when a resin collector is used.
[0019] 1.Negative electrode The negative electrode in the present disclosure has at least a negative electrode current collector. In addition, in the present disclosure, the negative electrode current collector is a resin current collector. As shown in FIG. 1, the negative electrode AN has a first metal layer 4A containing at least one of Mg and Ag between the negative electrode current collector 3 and the electrolyte layer EL. Also, as shown in FIG. 1, the negative electrode AN may have a second metal layer 4B between the negative electrode current collector 3 and the first metal layer 4A. On the other hand, although not particularly shown, it is preferable that the negative electrode does not have a negative electrode active material layer containing negative electrode active material particles.
[0020] (1) Negative electrode current collector The negative electrode current collector in the present disclosure is a resin current collector. The resin current collector means a current collector containing a resin as a main material. The ratio of the resin to all components constituting the resin current collector is, for example, 50% by weight or more, may be 60% by weight or more, 70% by weight or more, 80% by weight or more, 90% by weight or more, or 95% by weight or more. On the other hand, the above ratio of the resin is usually less than 100% by weight.
[0021] Examples of the resin used in the resin collector include thermoplastic resins, such as polyolefins, including polyethylene (PE) and polypropylene (PP).
[0022] The resin collector generally contains a conductive material. Examples of the conductive material include carbon materials. Examples of the carbon material include particulate carbon materials such as acetylene black (AB) and ketjen black (KB); and fibrous carbon materials such as carbon fiber, carbon nanotubes (CNT), and carbon nanofibers (CNF). The proportion of the conductive material in the resin collector is, for example, 5% by weight or more and 50% by weight or less.
[0023] The thickness of the resin current collector is not particularly limited, but is, for example, 1 μm or more and 500 μm or less.
[0024] (2) First metal layer The first metal layer in the present disclosure is disposed closer to the electrolyte layer than the negative electrode current collector. The first metal layer contains at least one of Mg and Ag. The first metal layer may contain Mg metal (simple Mg), Mg alloy (alloy mainly composed of Mg), Ag metal (simple Ag), or Ag alloy (alloy mainly composed of Ag). The metal other than Mg in the Mg alloy is preferably a metal that alloys with lithium, and examples of such metals include Zn and Al. The same applies to the metal other than Ag in the Ag alloy.
[0025] The first metal layer in the present disclosure is preferably in close contact with the negative electrode current collector. This is because the electron conductivity is improved. In other words, the first metal layer is preferably arranged so as to cover the surface of the negative electrode current collector. In the present disclosure, a member having a negative electrode current collector and a first metal layer arranged on the negative electrode current collector may be referred to as a coated current collector. In the coated current collector, the first metal layer may be arranged directly on the negative electrode current collector or may be arranged via another layer. As the other layer, for example, a second metal layer described later may be mentioned.
[0026] The first metal layer is, for example, a thin film, and is preferably a vapor deposition film. The thickness of the first metal layer is not particularly limited, but is, for example, 30 nm or more. On the other hand, the thickness of the first metal layer is, for example, 1000 nm or less, may be 800 nm or less, or may be 500 nm or less. The first metal layer can be formed by a vapor deposition method such as vacuum deposition.
[0027] The first metal layer may not contain Li, or may contain Li. The former corresponds to, for example, the state of the first metal layer in a battery before the first charge, and the latter corresponds to, for example, the state of the first metal layer in a battery after the first charge. As shown in FIG. 2, when Li is introduced into the first metal layer 4A by the first charge, the metals (Mg, Ag) contained in the first metal layer are alloyed with Li. In the first metal layer, an alloy phase such as an Mg-Li alloy phase or an Ag-Li alloy phase is formed. In addition, during discharge, Li moves from the first metal layer alloyed with Li to the positive electrode side. In addition, although not shown in particular, a Li phase may be formed inside the first metal layer 4A by charging. Similarly, a precipitated Li layer may be formed between the first metal layer and the electrolyte layer by charging. Similarly, a precipitated Li layer may be formed between the first metal layer and the negative electrode current collector by charging.
[0028] (3) Second metal layer The negative electrode according to the present disclosure may have a second metal layer disposed between the negative electrode current collector and the first metal layer and containing at least one of Ni and Cu.
[0029] The second metal layer may contain Ni metal (Ni simple substance), Ni alloy (alloy mainly composed of Ni), Cu metal (Cu simple substance), or Cu alloy (alloy mainly composed of Cu). Ni and Cu are metals that do not alloy with Li. The second metal layer is usually a layer that does not alloy with Li. Even if the first metal layer is alloyed with Li and, for example, the shape of the first metal layer is changed, the second metal layer that does not alloy with Li functions as a buffer layer, so that the electronic conduction path between the first metal layer and the negative electrode current collector is well maintained.
[0030] The second metal layer is, for example, a thin film, and is preferably a vapor deposition film. The thickness of the second metal layer is not particularly limited, but is, for example, 30 nm or more. On the other hand, the thickness of the second metal layer is, for example, 1000 nm or less, may be 800 nm or less, or may be 500 nm or less.
[0031] 2. Positive electrode The positive electrode in the present disclosure has a positive electrode current collector and a positive electrode active material layer.
[0032] The positive electrode active material layer contains at least a positive electrode active material, and may contain at least one of an electrolyte, a conductive material, and a binder.
[0033] The positive electrode active material may be, for example, an oxide active material. Examples of the oxide active material include LiCoO2, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, etc., rock salt layered active materials, LiMn2O4, Li4Ti5O 12 and olivine type active materials such as LiFePO4.
[0034] The conductive material is the same as that described in "1. Negative electrode". The electrolyte layer is the same as that described in "3. Electrolyte layer". Examples of binders include rubber-based binders such as butylene rubber (BR) and styrene butadiene rubber (SBR), and fluoride-based binders such as polyvinylidene fluoride (PVDF).
[0035] Examples of the material of the positive electrode current collector include SUS, aluminum, nickel, and carbon. Examples of the shape of the positive electrode current collector include a foil shape. The thickness of the positive electrode current collector is, for example, 1 μm or more and 500 μm or less.
[0036] 3. Electrolyte layer The electrolyte layer contains at least an electrolyte and may contain a binder.
[0037] Examples of the electrolyte include solid electrolytes. Examples of the solid electrolyte include inorganic solid electrolytes such as sulfide solid electrolytes, oxide solid electrolytes, and halide solid electrolytes. The sulfide solid electrolyte preferably contains sulfur (S) as the main component of the anion element. The oxide solid electrolyte preferably contains oxygen (O) as the main component of the anion element. The halide solid electrolyte preferably contains halogen (N) as the main component of the anion. Among these, the sulfide solid electrolyte is preferred.
[0038] Examples of sulfide solid electrolytes include Li2S-P2S5, Li2S-P2S5-LiI, Li2S-P2S5-GeS2, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-P2S5-LiI-LiBr, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, and Li2S-P2S5-Z. m S n(where m and n are positive numbers. Z is Ge, Zn, or Ga.), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li x MO y (where x and y are positive numbers, and M is P, Si, Ge, B, Al, Ga, or In.)
[0039] Other examples of solid electrolytes include organic solid electrolytes such as polymer electrolytes and gel electrolytes. Liquid electrolytes (electrolytic solutions) can also be used as electrolytes. In this disclosure, an electrolyte layer containing a solid electrolyte may be referred to as a solid electrolyte layer, and a battery having a solid electrolyte layer may be referred to as an all-solid-state battery. The binder is the same as that described in "2. Positive electrode". The thickness of the electrolyte layer is, for example, 1 μm or more and 500 μm or less.
[0040] In the battery, the solid electrolyte layer may be in direct contact with the first metal layer. Meanwhile, in the all-solid-state battery, another layer may be disposed between the solid electrolyte layer and the first metal layer. The other layer may be a protective layer that contains Sn and protects the solid electrolyte layer. The protective layer may contain Sn metal (single Sn) or may contain an Sn alloy (an alloy mainly composed of Sn). Au or Al may be used instead of Sn. The protective layer is, for example, a thin film, and is preferably a vapor deposition film. The thickness of the protective layer is not particularly limited, but is, for example, 30 nm or more. Meanwhile, the thickness of the protective layer is, for example, 1000 nm or less, may be 800 nm or less, or may be 500 nm or less. The protective layer may be formed, for example, by a sputtering method.
[0041] 4.Battery The use of the battery in the present disclosure is not particularly limited, but examples thereof include power sources for vehicles such as hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), electric vehicles (BEVs), gasoline automobiles, and diesel automobiles. In particular, it is preferable to use the battery as a driving power source for hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), or electric vehicles (BEVs). The battery may also be used as a power source for moving objects other than vehicles (for example, railways, ships, and aircraft), and may also be used as a power source for electrical appliances such as information processing devices.
[0042] The present disclosure is not limited to the above-described embodiment. The above-described embodiment is merely an example, and any configuration that is substantially the same as the technical idea described in the claims of the present disclosure and that exhibits similar effects is included in the technical scope of the present disclosure. EXAMPLES
[0043] [Example 1] (Preparation of resin collector) Resin (polyethylene), conductive material (acetylene black) and solvent (butyl butyrate) were mixed to obtain a resin slurry. The obtained resin slurry was applied onto a PET film by a blade method using an applicator. This was dried on a hot plate at 50°C for 20 minutes, and then further dried on a hot plate at 150°C for 30 minutes. The PET film was then peeled off to obtain a resin current collector (negative electrode current collector) with a thickness of 30 μm.
[0044] (Preparation of coated current collector) A 1000 nm-thick Mg layer (first metal layer) was formed on the surface of the obtained resin current collector by vapor deposition to obtain a coated current collector.
[0045] (Preparation of solid electrolyte layer) A Li2S-P2S5-based glass ceramic containing LiI was prepared as the sulfide solid electrolyte. The sulfide solid electrolyte and binder (a 5 wt% heptane solution of a PVdF-based binder) were added to heptane and stirred for 30 seconds using an ultrasonic disperser. After stirring, the mixture was shaken for 30 minutes to prepare a slurry. The prepared slurry was applied onto a PET film by the blade method using an applicator. This was allowed to dry naturally, and then dried on a hot plate at 100°C for 30 minutes. This resulted in a solid electrolyte layer on the PET film. The two obtained solid electrolyte layers were bonded together and coated with a 7 ton / cm 2 After pressing, the PET film was peeled off to obtain a free-standing solid electrolyte layer. A 100 nm-thick Sn layer was then formed on one side of the solid electrolyte layer by sputtering.
[0046] (Preparation of positive electrode) A solvent (butyl butyrate), a binder (a 5 wt% butyl butyrate solution of a PVdF-based binder), a positive electrode active material (lithium nickel cobalt aluminum oxide), and a conductive material were added to a PP container. Furthermore, the sulfide solid electrolyte was added so that the volume ratio of the positive electrode active material to the sulfide solid electrolyte was 75:25. Thereafter, the PP container was stirred for 30 seconds using an ultrasonic dispersion device (UH-50, manufactured by SMT). Next, the PP container was shaken for 30 minutes using a shaker (TTM-1, manufactured by Shibata Scientific Co., Ltd.). This resulted in the positive electrode slurry being obtained. The obtained positive electrode slurry was applied onto a positive electrode current collector (Al foil) by a blade method. Then, this was naturally dried, and further dried on a hot plate at 100°C for 30 minutes. This resulted in the positive electrode having a positive electrode current collector and a positive electrode active material layer.
[0047] (Preparation of evaluation battery) The coated current collector and the solid electrolyte layer were each punched out to Φ14.5 mm. Next, the solid electrolyte layer was placed on the coated current collector so that the Mg layer and the Sn layer faced each other. Furthermore, a positive electrode punched out to Φ11.28 mm was stacked so that the solid electrolyte layer and the positive electrode active material layer faced each other to obtain a laminate. A positive electrode terminal and a negative electrode terminal were connected to this laminate, and the laminate was sandwiched and welded. The laminate film was subjected to CIP treatment at a pressure of 392 MPa. This produced an evaluation battery.
[0048] [Example 2] An evaluation battery was prepared in the same manner as in Example 1, except that a 1000 nm thick Ni layer (second metal layer) was formed by sputtering before forming an Mg layer (first metal layer) on the surface of the resin current collector.
[0049] [Comparative Example 1] A battery for evaluation was produced in the same manner as in Example 1, except that a resin current collector (a resin current collector having no metal layer) was used instead of the coated current collector.
[0050] [Comparative Example 2] A battery for evaluation was produced in the same manner as in Example 1, except that a Ni foil (metallic current collector) was used instead of the coated current collector.
[0051] [Comparative Example 3] An evaluation battery was prepared in the same manner as in Example 1, except that a coated metal current collector was used in which a 1000 nm-thick Mg layer was formed on Ni foil (metal current collector) by sputtering instead of the coated current collector.
[0052] [evaluation] The evaluation batteries prepared in each Example and Comparative Example were restrained with a metal plate at a pressure of 1 MPa. These evaluation batteries were subjected to a test at 60°C, 3 to 4.2 V in CCCV mode, and 0.15 mA / cm 2 (0.03mA / cm 2 Charge and discharge tests were conducted under the condition of (100% cut). The coulombic efficiency was calculated from the charge and discharge capacities. The results are shown in Table 1.
[0053] [Table 1]
[0054] As shown in Table 1, Comparative Example 1 and Comparative Example 2 showed that the resin current collector had a lower Coulombic efficiency than the metal current collector. On the other hand, in Example 1 and Example 2, although a resin current collector was used, the Coulombic efficiency was better than that of Comparative Example 2 and Comparative Example 3. In particular, in Example 2, a high Coulombic efficiency of 89% was obtained. [Explanation of symbols]
[0055] 1...Positive electrode current collector 2...Cathode active material layer 3...Negative electrode current collector 4A…first metal layer 4B…Second metal layer CA…Positive electrode AN…Negative electrode EL…Electrolyte layer 10...battery
Claims
1. A battery that utilizes a deposition and dissolution reaction of metallic lithium as a negative electrode reaction, a positive electrode having a positive electrode current collector and a positive electrode active material layer, a negative electrode having at least a negative electrode current collector, and an electrolyte layer disposed between the positive electrode and the negative electrode; the negative electrode current collector is a resin current collector, The negative electrode has a first metal layer containing at least one of Mg and Ag between the negative electrode current collector and the electrolyte layer.
2. 2. The battery of claim 1, wherein the negative electrode has a second metal layer containing at least one of Ni and Cu between the negative electrode current collector and the first metal layer.
3. The battery according to claim 1 or 2, wherein the negative electrode current collector and the first metal layer form a coated current collector.
4. The battery of claim 1 or 2, wherein the first metal layer contains Li.
5. The battery of claim 1 or 2, wherein the first metal layer does not contain Li.
6. 3. The battery according to claim 1, wherein the electrolyte layer is a solid electrolyte layer containing a solid electrolyte.
Citation Information
Patent Citations
All-solid lithium ion secondary battery
JP2020087922A
Current collector, electrode for electric storage device, and lithium-ion secondary battery
WO2023053322A1
Lithium secondary battery
WO2023074845A1
Lithium solid type secondary battery and method for manufacturing the same
JP2016035867A
Cited By
All-solid-state batteries
JP2026512223A